1996
DOI: 10.1007/bf00242274
|View full text |Cite
|
Sign up to set email alerts
|

Immune system of cold-exposed and cold-adapted humans

Abstract: The aim of this study was to investigate whether or not the human immune system can be activated by a noninfectious stimulus, thereby improving the physiological status of the individual. The effect of a single cold water immersion (14 degrees C for 1 h) on the immune system of athletic young men, monitored immediately after immersion, was minimal. With the continuation of the cold water immersions (three times a week for a duration of 6 weeks) a small, but significant, increase in the proportions of monocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
100
2
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 22 publications
12
100
2
2
Order By: Relevance
“…Delahanty et al IL-6 response. Our finding that plasma concentrations of IL-6 rose in response to cold exposure is in contrast to the work of Jansky et al (53). They reported a slight and 77 non-significant trend to a reduction in the concentration of IL-6 when subjects were immersed for 1 h in cold (14°C) water.…”
Section: Effects Of Passive Heating and Moderate Exercise (With And Wcontrasting
confidence: 99%
“…Delahanty et al IL-6 response. Our finding that plasma concentrations of IL-6 rose in response to cold exposure is in contrast to the work of Jansky et al (53). They reported a slight and 77 non-significant trend to a reduction in the concentration of IL-6 when subjects were immersed for 1 h in cold (14°C) water.…”
Section: Effects Of Passive Heating and Moderate Exercise (With And Wcontrasting
confidence: 99%
“…Published data suggest that WBC has no detrimental effect on immunological parameters, although the observation period in this study was too short to evaluate changes in lymphocyte involvement and function. Long-term cold water immersion of healthy males is known to produce slight increases in plasma TNFa, lymphocytes and monocytes (Jansky et al, 1996) Specific studies on immunoglobulins during and after WBC are lacking, however.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated that WBC does not enhance hematological values, as measured by hemoglobin concentration and counts of erythrocytes, reticulocytes, leukocytes, and platelets in peripheral blood (Banfi et al, 2008). Studies investigating the effects of cold exposure on immune function (Walsh and Whitham, 2006) found that lymphocyte, monocyte and tumor necrosis factor a levels were increased, whilst concentrations of interleukins IL-6, IL-1b, and C-reactive protein (CRP) were unchanged after 6 weeks of cold water immersions (Jansky et al, 1996). Moreover, resting levels of IL-6, lymphocytes and monocytes were noted to be higher in subjects accustomed to winter swimming than in inexperienced individuals (Dugué and Leppä nen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The response of the body to cold temperatures occurs through changes in the endocrine system (increase in adrenocorticotropin concentration, β-endorphins, epinephrine, norepinephrine and testosterone concentration in men) [1][2][3][4], circulatory system (contraction of blood vessels in the skin, then their dilation and congestion of the skin) [5], neuromuscular system (reduction of muscle tension, decrease in nerve conduction velocity) [6] and immunological system (increase in cell-mediated and humoral immunity) [1,[7][8][9][10]. Moreover, whole body cooling influences the prooxidant-antioxidant balance in blood [11][12][13][14], and has an anti-inflammatory [15] as well as an analgesic effect [6].…”
Section: Introductionmentioning
confidence: 99%